The Correlation between the Performance of Some Basic Skills and the Level of Cognitive Achievement of handball Players - Hossam Ghaleb Abdulhussein (Journal of Global Pharma Technology, 2016)
The importance of research in the analysis of the level of cognitive achievement and its relation to the skillful performance of handball game to improve the level of the game and thus benefit the acquisition of knowledge and theoretical information related to the game plans, which is generated through the explanation and theoretical discussions of the positions of the athlete during the application of skill or sports competition.The research aims atDesign a form for the collection of knowledge with indicators (law, Shoot, plans) for players who advance handball.Build a test for the scientific knowledge collection of players who advance handballTo identify the relationship between the achievement of knowledge of the players and the performance of some basic skills handball.The hypotheses of the research were:There are differences of statistical significance in scientific knowledge and the performance of some basic skills of handball.There is a significant relationship between the level of cognitive achievement and the performance of some basic skills of handball.The research areas were:Human Field: Al Qasim Club players in the Premier League handball.Time domain: from 12/1/2017 until 14/3/2017.Spatial space: the forum of youth of the denominator.The conclusions wereThere is a significant correlation between the cognitive achievement of the three axes and the following skills (handling, correction of jumping, defense moves, and wall of resistance).Keywords: Performance, Basic skills and cognitive achievement.